Edukasi Gaya Hidup Sehat Terkait Penyakit Hipertensi - setiyanto, Riyan; P, Yunita Dian; Ramadhani, Silviana Rhokimatul; Lutfianawati, Nisa; Khunaisa, Khunaisa (Bengawan : Jurnal Pengabdian Masyarakat, 2025)
Hypertension, known as the silent killer, is a non-communicable disease whose prevalence continues to increase globally and nationally. The prevalence of hypertension in the Indonesian population aged ≥18 years has reached 34.1%. The main risk factors for hypertension include excessive salt consumption, obesity, lack of physical activity, and psychosocial stress, all of which are greatly influenced by a person's diet and lifestyle. This community service activity was carried out through community outreach aimed at providing knowledge about hypertension so that the public can take preventive measures. The results of the health outreach to the community about hypertension that has been carried out have increased participants' knowledge of hypertension, better managing their diet and lifestyle, and understanding the signs and symptoms and ways to prevent hypertension. Keywords: Hypertension; Prevalence; silent killer.